Willing or reluctant to share health data? A moderated mediation analysis of wearable device usage and data-sharing intentions among older adults - Luxi Zhang; Qingqing Xie; Sha Qiu; Muhan Liu; Fei You; Xinshu Zhao (Digital Health)
Background Digital health has the potential to enhance health communication efficiency. However, this potential remains underappreciated among older population due to prevalent technological challenges. The introduction of wearable devices may constitute a positive intervention to alleviate these technological concerns and improve health communication. This study aims to investigate the association between wearable device usage and health tracking data sharing intention among older adults, with digital technology self-efficacy serving as a mediator. Methods This study used cross-sectional secondary data from the Health Information National Trends Survey (HINTS 5 Cycle 4), conducted between February and June 2020. The sample included older adults aged 60 or older ( n  = 1521). Statistically significant relationships among wearable devices, digital technology self-efficacy, and health tracking data sharing intention were examined using SPSS bootstrapping procedures. Results The results indicate that wearable device usage, when mediated by digital technology self-efficacy, has both direct and indirect positive effect on health tracking data sharing intention ( bp  = .742, p  < .001; bp  = .006, p  < .05). In addition, for moderating effect, older adults who perceived social support exhibit a stronger influence on the relationship between digital technology self-efficacy and health tracking sharing ( bp  = .132, p  < .05). Conclusion This study provides empirical evidence that wearable devices play an important role in improving digital technology self-efficacy and ultimately contribute to health tracking data sharing among older adults. Understanding these relationships can encourage wearable device adoption and improve health communication and well-being among the older population in the era of digital health.